The Processing Mechanism of Repetitive Practice Affecting Time-Based Prospective Memory - Jiaqun Gan; Yunfei Guo; Enguo Wang (Behavioral Sciences, 2023)
Time-based prospective memory (TBPM) refers to performing intended actions at a specific time in the future. The TBPM task is very common in daily life, and whether it can be successfully completed can affect our quality of life. Repeated behavior training can usually improve social cognitive performance, and this study focused on exploring whether TBPM performance could improve with repeated behavior training. Meanwhile, we also focused on whether behavior training could reduce attention consumption, both internal and external, attention on TBPM tasks. In this study, a single-factor between-subject design was adopted. Seventy-three undergraduates were assigned to three groups: the control group, the baseline group, and the experimental group. The baseline group only needs to perform ongoing tasks, so the ongoing task performance of the control group will not be affected by TBPM tasks. The control group needs to perform both ongoing and TBPM tasks without practice. The experimental group needs to perform both ongoing and TBPM tasks after 30 exercises. The ongoing task is a typical working memory task. The TBPM task was to press a “1” button every 1 min. The results showed that the performance of ongoing tasks in the baseline group, experimental group, and control group decreased sequentially, and the experimental group had less time monitoring than the control group. The results indicated that behavior training could reduce attention consumption in both internal attention and external attention, but it could not reach the level of automatic processing.